ADVANTAGES OF THE IMPLEMENTATION OF HR-ANALYTICS IN ENTERPRISE MANAGEMENT - BAKSALOVA, Olha; GLUSHKO, Tanya; HORBATIUK, Oleksandr; KOSHONKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article substantiates the implementation of HR-analytics in the activities of modern enterprises in order to increase the efficiency of the work of structural divisions involved in personnel work. The role of HR analytics in the process of personnel management is considered, the use of HR indicators is proposed, which greatly simplifies the assessment of the performance of personnel departments at various levels and, ultimately, predicts and evaluates the results of their work. The issue of efficiency is one of the key issues in almost all business processes. If a choice needs to be made in conditions of limited resources: what is better to spend money on, then it is impossible to do this without measuring efficiency. This also applies to HR services. In connection with the growth of requirements for effective personnel management at enterprises, the question of how to evaluate the activities of the personnel service in order to determine the required number of its employees and evaluate the effectiveness of their activities is becoming relevant. At the same time, the evaluation of personnel management services should be related to the tasks of the enterprise and stimulate personnel specialists to perform their work in the most effective way. The article also analyzes the problems of applying HR metrics in the practice of modern domestic enterprises. The advantages of HR analytics for HR and business activities have been determined. It was found that the variety of functions and tasks of personnel work units, the lack of practice of accumulating primary data, which are adapted to the direction of the company’s industry, greatly complicate the metric analysis of the effectiveness of HR activities as a whole. That is why there is a need to describe and systematize indicators of HR activity in order to facilitate their integration into the work of a modern HR department. For the effective implementation of the HRM system at the enterprise, it is very important to use HR analytics tools. This practice will allow to more accurately determine the vectors of strategic response to achieve the goals of controlling business activity. Thus, HR analytics is the key to successful organizations that have the necessary resources to invest in complex information systems and are able to attract and develop effective skills for monitoring analytical data. Most of these organizations create opportunities for HR analytics in order to achieve a competitive advantage by analyzing data about their workforce. But the ability of human resources units to influence these processes is often limited, therefore the issue of the prospects for activating this function in Ukraine, taking into account the world experience in this field, is actualized.